Using smartwatches to facilitate a group dynamics-based statewide physical activity intervention. Issue 142 (October 2020) - Esakia, Andrey; McCrickard, Scott; Harden, Samantha; Horning, Michael; Ramalingam, NithyaPriya
Highlights: Updates on smartwatch watchfaces establish awareness of physical activity levels. Users react to group related feedback on the watchface by engaging in physical activity. Watchface updates can mediate group dynamics. Users regularly glance at the watchface and notice wellness related indicators. Abstract: Physical inactivity is a major cause of disease, both in the United States and globally. Physical activity interventions often use a multi-level and community-based approach combining individual and group-based behavioral strategies to promote physical activity and influence social norms. Such interventions can increase their impact by adopting technology-based solutions to facilitate the underlying behavioral strategies. Current technologies for persuading physical activity primarily focus on facilitating individual-level behavioral strategies and de-emphasizing interpersonal aspects. This article focuses on the design and evaluation of technology aimed at facilitating group dynamics-based strategies for promoting physical activity within small socially-connected teams. This work introduces a multi-component smartwatch-centered system called FitAware that uses sensors to automatically track physical activity and leverage the advantages of the watch form factor to facilitate both group and individual level behavioral strategies via non-interruptive, glanceable, and frequent updates. This article describes the design and evaluation of FitAware in the context of an 8-week statewide physical activity community-based intervention.